Efficacy, Safety, Quality Assurance of Isomers of Non-Steroidal Anti-Inflammatory Drugs: Dexketoprofen and Dexibuprofen - Elena Litvinova; Mariya Zarichkova; Svitlana Kovalenko; Olga Posylkina; Olena Tkachenko; Anastasiia Lisna (Journal of Global Pharma Technology, 2020)
The aim of this work is to analyze and systematize data on efficacy, safety, and quality assurance for NSAID isomers – dexketoprofen and dexibuprofen. Studies were conducted using databases on the Internet: PubMed; Food and Drug Administration, European Medicines Agency. It has used retrospective, logical, systematic and analytical methods. The results of a multifaceted analysis of sources of data of clinical use proved the high analgesic efficacy of dexketoprofen and dexibuprofen in acute and chronic pain of various etiologies, such as toothache, dysmenorrhea, pain after surgery, muscle pain, headache, back pain, pain from bone metastases, etc. To achieve the effect obtained with the use of 1 dose of racemic NSAIDs, half the dose of their active isomers is sufficient. The high clinical effectiveness of dexketoprofen, dexibuprofen combines with their relative tolerance, in particular from the gastrointestinal tract. In large part, the safety of dexketoprofen is due to the presence of only the active S (+) - enantiomer of ketoprofen, dexibuprofen is due to the presence of only active S (+) - ibuprofen, which eliminates the side effects associated with the influence of the R (-) - enantiomers. The results of the analysis of quality assurance of generic dexketoprofen (class 1 of biopharmaceutical classification system) and dexibuprofen (class 2 of biopharmaceutical classification system) during the biowaiver procedure are systematized. It has been shown that not only high permeability and high solubility, but also the composition of the drug excipients are important for pharmaceutical equivalence in vitro. Based on the results research findings presented, it is possible to optimize the technological process and analytical methods, which allows taking into account critical factors and ensuring the quality of the medicine and its bioequivalence to the reference drug.